El ojo de jade - Liang, Diane Wei, 1966-; Diez, Lola; Liang, Diane Wei, 1966- (Madrid : Ediciones Siruela, 2010)
A tale set in modern Beijing follows a detective's search for a missing artifact, in a case that illuminates less-favorable aspects of Chinese culture and the detective's own family during the Cultural Revolution.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: Mei, Wang -- (Fictitious character) -- Fiction; Women private investigators -- China -- Beijing -- Fiction; China -- Antiquities -- Fiction; China -- History -- Cultural Revolution, 1966-1976 -- Fiction; Beijing (China) -- Fiction; Detective and mystery fiction; Electronic books